ANALISIS PEMANFAATAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN IPA DALAM MENINGKATKAN MINAT BELAJAR SISWA SD - Aviatunnur, Siddikah; S. Putra, Karantiano; Hakim, Abdul; Oktavia Wahyuni, Siva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology in the modern era encourages the use of various innovative learning media, one of which is YouTube. The YouTube platform has significant potential as a learning medium in achieving the Natural Science (IPA) learning process in elementary schools. This study aims to analyze the use of YouTube as a science learning medium in increasing student learning interest. This study uses a qualitative approach with a literature review method by examining various relevant literature sources, such as articles, scientific journals, books and previous research results. The results of the study indicate that YouTube as an audiovisual-based learning medium has the advantage of presenting material in an interesting, contextual, and easy-to-understand manner for students. In the process, it can help visualize abstract concepts so that they become more concrete. This can have a positive impact on increasing student learning interest, which is characterized by increased attention, curiosity and active participation in teaching and learning activities. In addition, the use of YouTube can accommodate differences in student learning styles through the presentation of visual elements and complementary audio elements. From the visual side, the material is presented in the form of images, animations, and demonstrations that help students understand science concepts. Meanwhile, the audio side, which contains explanations delivered through supporting voice-overs, can clarify information and help students follow the material more systematically. Both of these features facilitate students' development of a more comprehensive understanding. However, its effectiveness depends heavily on the teacher's role in content selection, learning management, and media integration with appropriate learning strategies.